Hubungan Status Gizi Dengan Kejadian Anemia Pada Ibu Hamil Trimester III Di BPS Hj Sri Sulasmiati, S.ST Desa Wonoayu Kec. Pilangkenceng Kab. Madiun - Dyah Permatasari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2013)
Anaemia instance really been regarded by pregnant mother nutrient state that alone. Nutrient on useful pregnant mother to get intrauterine aught fetus growth to keep health and alone mother body force, so don't ensue fatal on pregnant mother and newborn baby. This research intent to study relationship among nutrient state with anaemia instance on trimester's pregnant mother III. at BPS Hj Sri Sulasmiati, S.ST Wonoayu‟s Kec's Village Pilangkenceng Madiun‟s. Design observationaling to utilize analytic observasional with approaching cross sectional. Independent's variable which is nutrient state, dependent's variable which is anaemia instance. Its population is exhaustive trimester's pregnant mother III. at BPS Hj Sri Sulasmiati, S.ST Wonoayu Village. Mojosari Kab. Madiun as much 32 pregnant mothers. Sample 32 respondent that took by tekhnik sampling Non Probability sampling type Accidental is sampling. Date downloading May 15 15th June checklist's research instrument and Hb Sahli Set. Quiz statisticaling to utilize quiz spearman rank with a = 0,05. Observational result to be gotten that largely respondent good nutrient state which is 19 respondents (59,4 %) and 15 respondents (46,9 %) don't experience anaemia.. Morphological result by tests spearman rank with a = 0,05 are gotten that rs = 0,666789 rs's matters computing > 0,364, therefore Ho is refused and Hi is accepted therefore there is relationship among nutrient state with anaemia instance on trimester's pregnant mother III. at BPS Hj Sri Sulasmiati, S.ST Wonoayu's Village Pilangkenceng Madiun‟s district Year 2013. Conclusion this research is available subjective among nutrient state with anaemia instance on trimester's pregnant mother III. at BPS Hj Sri Sulasmiati, S.ST Wonoayu's Village Pilangkenceng Madiun's. We as officer of health moring to increase service to mother nutrient state pregnant trimester III.ING to anticipate its happening anaemia.